2015
DOI: 10.1007/s13277-015-3439-6
|View full text |Cite
|
Sign up to set email alerts
|

Japonicone A inhibits the growth of non-small cell lung cancer cells via mitochondria-mediated pathways

Abstract: Japonicone A, which is a natural product isolated from the aerial part of Inula japonica Thunb., has a wide range of clinical applications, including anti-inflammation and anti-oxidation. This study investigated the effects of japonicone A on the growth of non-small cell lung cancer (NSCLC) cell lines. The results showed that japonicone A significantly inhibited the growth of NSCLC cell lines in a dose- and time-dependent manner. This product also blocked cell cycle progression at S phase and induced mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The initiation of the intrinsic pathway is associated with pro-apoptotic factors, including B-cell lymphoma 2 (Bcl-2)-associated X protein and Bcl-2-associated death promoter, which leads to an increased permeability of the mitochondria membrane, loss of membrane potential and the release of cytochrome c into the cytosol (20). The intrinsic pathway is associated with activated caspase-3, whereas the extrinsic pathway is associated with the activation of caspase-8 (21). In the results of the present study, it was indicated that the relative activities of caspase-8 remained unchanged (data not shown), therefore it may be that the intrinsic pathway was involved in the process, which is a focus of future study.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of the intrinsic pathway is associated with pro-apoptotic factors, including B-cell lymphoma 2 (Bcl-2)-associated X protein and Bcl-2-associated death promoter, which leads to an increased permeability of the mitochondria membrane, loss of membrane potential and the release of cytochrome c into the cytosol (20). The intrinsic pathway is associated with activated caspase-3, whereas the extrinsic pathway is associated with the activation of caspase-8 (21). In the results of the present study, it was indicated that the relative activities of caspase-8 remained unchanged (data not shown), therefore it may be that the intrinsic pathway was involved in the process, which is a focus of future study.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that JapA is safe and effective in treating other human cancers containing high expression levels of MDM2, e.g. , Burkitt lymphoma and lung cancer [ 20 21 ]. Mechanistically, JapA decreases MDM2 protein stability and inhibits MDM2 transcription, regardless of p53 status of the cells or tumors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition antiinflammatory properties of Tanacetum vulgare [27], Inula helenium L [28], Melissa officinalis [17], Artemisia vulgaris L [29] can all increase oxidative stress and induce mitochondrial-related apoptosis. These compounds have been traditionally used in anti-cancer therapy.…”
Section: Resultsmentioning
confidence: 99%